A Zn‐Based Metal‐Organic Framework Modified by CuCl2 Under Ambient Conditions for Simultaneous Ultrasonic‐Assisted Removal of Pb and Cd Ions with Fast Kinetics from Aqueous Solution. Issue 12 (22nd March 2023) - Mojtahedi, Niloufar; Zare‐Dorabei, Rouholah; Hossein Mosavi, Seyed
Abstract: Water pollution has become one of the most severe issues due to the growth of various industries and increased urbanization. Heavy metals are a contaminant that has sparked widespread concern in recent decades. Both natural and human activities cause heavy metal accumulation in the environment. They have a wide range of adverse impacts on the environment and the health of living organisms. Because of its simplicity, high speed, and cost‐effectiveness, adsorption is the most widely used heavy metal removal method. In this study, a metal‐organic framework MOF‐5 modified by CuCl2 was used as an adsorbent to simultaneously remove lead and cadmium heavy metal ions. The structure was identified using scanning electron microscopy (SEM), an X‐ray diffraction pattern (XRD), Fourier transforms infrared spectroscopy (FT‐IR), thermogravimetric analysis (TGA), and nitrogen adsorption and desorption analysis (BET). The central composite design was applied to achieve the optimum adsorption conditions. The optimum conditions were pH=7, the adsorbent dosage of 8 mg, a three‐minute lead concentration of 79 mg/L, and a cadmium concentration of 19 mg/L in the experimental design software. Lead and Cadmium RSD was 1.42 % and 2.3 %, respectively. Abstract : This method has advantages such as the ability to perform the experiment at ambient temperature and pressure, easy and fast synthesis of adsorbent, rapid adsorption compared to other methods, the ability to regenerate well, and being cheap.